KESEHATAN REPRODUKSI PEKERJA WANITA* - Muhadjir Darwin; Mahendra Wijaya (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
As a society becomes more modernized, the role of women in a working place is increasing. A quite large number of women work in various sectors: agriculture, industry, and services. While their participation contributes to the welfare of their family and society at large, the health implication (particularly on reproductive health) needs considerable attention. The study shows the incidence of various reproductive health problems in a working place and low attention given by the employers to this problem. Statutes and government regulations have been made to protect female labours from reproductive health problems, but these laws and regulations have not been implemented consistently by the employers. This studyproposes to increase the government control on reproductive health services and protection given by employers to private industries, and to give the workers the right to organize themselves so that they can obtain the power to have reproductive health services as well as protection from their employers.